2020
DOI: 10.3390/catal10060647
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Step Process for the Bioconversion of Whey Permeate into a Glucose-Free D-Tagatose Syrup

Abstract: We have developed a sustainable three-stage process for the revaluation of cheese whey permeate into D-tagatose, a rare sugar with functional properties used as sweetener. The experimental conditions (pH, temperature, cofactors, etc.) for each step were independently optimized. In the first step, concentrated whey containing 180–200 g/L of lactose was fully hydrolyzed by β-galactosidase from Bifidobacterium bifidum (Saphera®) in 3 h at 45 °C. Secondly, glucose was selectively removed by treatment with Pichia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Most likely, in one of them, the two fructose units should be linked by a β-(2-6) bond due to the preference of RdINV to form 6-kestose, a levan-type trisaccharide where fructose units are connected by this linkage. The possibility of using P. pastoris cells to remove glucose [43] and fructose from the reaction mixtures is a very attractive possibility in order to obtain suitable FOS mixtures for diabetic patients, which we also intend to evaluate in the future. Moreover, some of the evaluated disaccharides were also fructosylated (Table 3): among them, palatinose and trehalose, which shared this characteristic with the β-fructofuranosidase from X. dendrorhous, but not with that from Sch.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, in one of them, the two fructose units should be linked by a β-(2-6) bond due to the preference of RdINV to form 6-kestose, a levan-type trisaccharide where fructose units are connected by this linkage. The possibility of using P. pastoris cells to remove glucose [43] and fructose from the reaction mixtures is a very attractive possibility in order to obtain suitable FOS mixtures for diabetic patients, which we also intend to evaluate in the future. Moreover, some of the evaluated disaccharides were also fructosylated (Table 3): among them, palatinose and trehalose, which shared this characteristic with the β-fructofuranosidase from X. dendrorhous, but not with that from Sch.…”
Section: Discussionmentioning
confidence: 99%
“…22c, attaining a yield of 30%. Recently, Cervantes et al [172] reported the use of microbial fermentation to produce a d-tagatose syrup from whey permeate. Initially, lactose was hydrolyzed using B. bifidum β-galactosidase, and then the glucose generated was removed by contacting the hydrolyzed whey-permeate with P. pastoris cells.…”
Section: Microbial Selective Fermentationmentioning
confidence: 99%
“…Although the metabolism of resting cells hibernates due to the lack of main carbon and nitrogen sources, sometimes compounds derail their planned synthetic schemes, giving rise to unwanted products that damage the process selectivity. As an alternative to resting cells, cell-free enzyme systems ameliorate these selectivity issues since one strictly uses the enzymes participating in the synthetic route 13 . However, working with isolated enzymes entail some Please do not adjust margins Please do not adjust margins Please do not adjust margins stability burdens due to the fragility of soluble enzymes under operational conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we approach the biosynthesis of serinol from glycerol through a two-step sequential process combining G. oxydans resting cells and an immobilised amine transaminase from Pseudomonas fluorescens (Pf-ATA). Serinol is an important building block in synthetic chemistry that is found in many bioactive compounds (sphingosines, ceramides) and pharmaceuticals [13][14][15] . Despite its interest, serinol biosynthesis is underexplored in applied biocatalysis and the few works on this topic rely on fermentative processes using glycerol and glucose as starting materials.…”
Section: Introductionmentioning
confidence: 99%